Orbital and spectral analysis of the benchmark brown dwarf HD 4747B - Peretti, S; Ségransan, D; Lavie, B; Desidera, S; Maire, A; D'Orazi, V; Vigan, A; Baudino, J; Cheetham, A; Janson, M; Chauvin, G; Hagelberg, J; et al. (EDP Sciences, 2019)
Context. The study of high-contrast imaged brown dwarfs and exoplanets depends strongly on evolutionary models. To estimate the mass of a directly imaged substellar object, its extracted photometry or spectrum is used and adjusted with model spectra together with the estimated age of the system. These models still need to be properly tested and constrained. HD 4747B is a brown dwarf close to the H burning mass limit, orbiting a nearby (d = 19.25 ± 0.58 pc), solar-type star (G9V); it has been observed with the radial velocity method for over almost two decades. Its companion was also recently detected by direct imaging, allowing a complete study of this particular object. Aims. We aim to fully characterize HD 4747B by combining a well-constrained dynamical mass and a study of its observed spectral features in order to test evolutionary models for substellar objects and to characterize its atmosphere. Methods. We combined the radial velocity measurements of High Resolution Echelle Spectrometer (HIRES) and CORALIE taken over two decades and high-contrast imaging of several epochs from NACO, NIRC2, and SPHERE to obtain a dynamical mass. From the SPHERE data we obtained a low-resolution spectrum of the companion from Y to H band, and two narrow band-width photometric measurements in the K band. A study of the primary star also allowed us to constrain the age of the system and its distance. Results. Thanks to the new SPHERE epoch and NACO archival data combined with previous imaging data and high-precision radial velocity measurements, we were able to derive a well-constrained orbit. The high eccentricity (e = 0.7362 ± 0.0025) of HD 4747B is confirmed, and the inclination and the semi-major axis are derived (i = 47.3 ± 1.6°, a = 10.01 ± 0.21 au). We derive a dynamical mass of mB = 70.0 ± 1.6 MJup, which is higher than a previous study but in better agreement with the models. By comparing the object with known brown dwarfs spectra, we derive a spectral type of L9 and an effective temperature of 1350 ± 50 K. With a retrieval analysis we constrain the oxygen and carbon abundances and compare them with the values from the HR 8799 planets.